Internet of Things (IoT) application in the Malaysian construction industry: the types and challenges during construction stage / Nur Airin Amira Zuhairinizam and Dr. Ani Saifuza Abd Shukor - Zuhairinizam, Nur Airin Amira; Abd Shukor, Ani Saifuza (College of Built Environment, 2023)
Construction Industry Development Board (CIDB) has already introduced the Construction 4.0 Strategic Plan for the year 2021 until 2025, focusing on the industrial revolution 4.0 to meet the standard of future development that is predicted to be more technological.